Rosuvastatin Lowers Systemic Inflammatory Response in Coronary Artery Bypass Graft Accompanied by Cardiopulmonary Bypass Surgery: A Randomized Controlled Study - Ozguler, Ibrahim M.; Burma, Oktay; Uysal, Ayhan; Akbulut, Handan (Canadian Soc Clinical Investigation, 2015)
Purpose: Cardiopulmonary bypass (CPB) is commonly associated with a systemic inflammatory response that may lead to severe complications. Classic signs of systemic inflammatory response syndrome are complement activation and changes in cytokine and acute phase reactant levels. The effects of rosuvastatin after CPB on interleukin-6 (IL-6), interleukin-10 (IL-10), interleukin-18 (IL-18) and High Sensitivity C-Reactive Protein (hs-CRP) levels were investigated. Methods: Thirty-seven male and thirteen female patients (total=50) aged 42 to 78 years, who had coronary bypass surgery due to coronary artery disease were randomly divided into two groups. The 25 patients in the control group were administered placebos. The 25 in the treatment group were administered 20 mg rosuvastatin tablets daily between preoperative day 7 and postoperative day 28. Blood samples were taken at six time points; before induction of anesthesia (T1), during CPB (T2), five minutes after removal of cross clamp (T3), after protamine infusion (T4), postoperative day three (T5) and postoperative day 28 (T6). Data points were expressed as mean +/- standard deviation (SD). Results: Rosuvastatin lowered IL-6 levels at T4, T5 and T6 time points (T4, T5, T6 p < 0.05), and elevated IL-10 levels at T3 and T4 (T3, T4 p < 0.05). IL-18 levels were also elevated at multiple time points. Rosuvastatin also lowered hs-CRP levels and cholesterol levels at T6 (p < 0.05). Conclusion: Administering 20 mg/day of rosuvastatin between preoperative day 7 and postoperative day 28 may result in fewer complications in certain (especially intraoperative) cases of systemic inflammatory response caused by the CPB technique used in coronary bypass surgery.
Keywords: Gamma-Inducing Factor; Endothelial Function; Il-18; Pretreatment; Injury; Lipoprotein; Myocardium; Ischemia; Risk